Review And Analysis On Hybrid Control Of Fault Ride Through And Transient Stability Of Vsc-Hvdc (Journal of Pharmaceutical Negative Results, 2022)
A steady DC-Link Voltage, a CV voltage control and a reactive power control on the basis of the previous reviewers' analysis are the goals of the VSC-HVDC connecting controller. In order to achieve these objectives, the appropriate controller is required at both VSC-HVDC terminals. This paper presents a non-linear control approach to improve the VSC-HVDC relationship's control robustness. A sliding mode control (SMC) and an integrated proportional control (PI) were used for the configuration of a hybrid controller. The hybrid controller will provide mathematical simulation. This hybrid driver provides malfunction driving and the transient reliability of the VSC-HVDC link. This paper presents a non-linear approach to control to improve the robustness of the VSC-HVDC controller. The hybrid controller configuration is a control of the sliding mode (SMC) and an integrated proportional control (PI) for a hybrid controller design. Fault ride the stability of this hybrid control unit is provided through and transient VSC-HVDC links. MATLAB and Simulink simulate the hybrid controller and increases the performance of the controller. The simulation induces a symmetrical grid-side malfunction to maintain transient stability.